Genetic Architecture of Yield Components in Toria - Kumar, Prakash; Yadav, T P; Raj, Lekh; Thakral, N K (Annals of Arid Zone, 2016)
Diallel analysis. carried out with six inbred lines of toria (Brassica campestris L. var. Toria). indicated the presence of both additive and non-additive genetic components with the latter being more important for length of main raceme and 1OOO-seed weight. The ratio (HI/D)0.05 showed the prese!lce of over-dominance for all the traits. Parents Sangam. TS-61 TH-68 and TC-113 possessed significant gca effects for two or more than two traits at a time and were considered as superior. Likewise, crosses. white flower x TH-68 and Sangam x Tobin attained significant sea effects for most of the component traits and adjudged superior.